ACTINOMYCES NAESLUNDII ISOLATED FROM BONE MARROW BIOPSIES OBTAINED FROM PATIENTS WITH MALIGNANT LYMPHORETICULAR DISEASES - I.Mobedi; J.Vandyoussefi; H.Rassa; HA.Fardin (Tehran University of Medical Sciences, 1981)
Different types of Actinomyces spp isolated from the oral cavity of human in healthy as well as in pathological state. Internally it is only found in association with pathological organs. Recently Actinomyces naeslundii has been isolated from blood culture of a leukemic patient. Present studies indicate the association of this microorganism with cells obtained from bone marrow by punction in more than 40 percent of patients of patients with malignant lymphoreticular disease.